FAUNAL AFFINITY OF TOARCIAN-AALENIAN (EARLY JURASSIC) BIVALVES FROM MAE SOT AND UMPHANG (TAK PROVINCE), NORTHWESTERN THAILAND - Kozai T.; Hirsch F.; Ishida K.; Meesook A. (My University, 2006)
In the Mae Sot and Umphang areas (NW Thailand), Jurassic strata seal the Permian and Triassic substratum of the Shan-Thai terrane with a brecciated conglomerate. Pliensbachian to Early Bajocian shallow marine strata are intercalated within the partly terrestrial Jurassic sequence. Thirty-five Toarcian-Aalenian bivalve species from Mae Sot and Umphang were identified. Among these,Eomiodon chumphonensis Hayami is known only from Thailand, whereasParvamussium donaiense (Mansuy),Myophoriella saurini Hayami,Thracia loducensis Hayami,Pholadomya (Bucardiomya) fontainei Hayami,Thracia loducensis Hayami andModiolus sestiniae Hayami were originally described in Vietnam.M. sestiniae also occurs in Iran. The greater part of the fauna, however, shows varying degrees of affinity with Myanmar (6 species), Cutch (10 species), Japan (13 species) and Europe (9 species), Levant (2 species). In view of these, it appears that these highly endemic Toarcian-Aalenian bivalves from Thailand characterize the Southeastern Asian Province of Tethys.
Keywords: TOARCIAN-AALENIAN; JURASSIC; MARINE BIVALVES; THAILAND; SE ASIAN PROVINCE; Mesozoic::Jurassic::Lower::Toarcian; Мезозой::Юрская::Нижний::Тоарский; Mesozoic::Jurassic::Middle::Aalenian; Мезозой::Юрская::Средний::Ааленский